Analysis and Design of Timing Recovery Schemes for DMT Systems over Indoor Power-Line Channels. (22nd May 2007) - Cortés Cortés, José Antonio José Antonio; Díez Díez, Luis Luis; Martos-Naya Martos-Naya, Eduardo Eduardo; Cañete Cañete, Francisco Javier Francisco Javier; Entrambasaguas Entrambasaguas, José Tomás José Tomás
Abstract : Discrete multitone (DMT) modulation is a suitable technique to cope with main impairments of broadband indoor power-line channels: spectral selectivity and cyclic time variations. Due to the high-density constellations employed to achieve the required bit-rates, synchronization issues became an important concern in these scenarios. This paper analyzes the performance of a conventional DMT timing recovery scheme designed for linear time-invariant (LTI) channels when employed over indoor power lines. The influence of the channel cyclic short-term variations and the sampling jitter on the system performance is assessed. Bit-rate degradation due to timing errors is evaluated in a set of measured channels. It is shown that this synchronization mechanism limits the system performance in many residential channels. Two improvements are proposed to avoid this end: a new phase error estimator that takes into account the short-term changes in the channel response, and the introduction of notch filters in the timing recovery loop. Simulations confirm that the new scheme eliminates the bit-rate loss in most situations.